Factor Analysis of Influence of Purchase Intention on the Sociolla Platform - Jeanne Carine; Desman Hidayat; Erick Fernando (Journal of E-business and Management Science, 2023)
Purchase intention arises in a person planning to buy a product which includes the goods or services to be used. Several factors can influence purchase intention, including price, consumer reviews, and brand image, which can affect customer trust. The population of this study is Sociolla users, while the sample of this study is individuals who have the Sociolla application and have made purchases through Sociolla at least once. Data was collected using a questionnaire filled out by respondents who met the sample criteria. This study uses the path analysis method by measuring the direct and indirect effects between variables. The results show that consumer reviews and brand image positively and significantly influence trust. Meanwhile, price and brand image positively and significantly influence purchase intention. Price doesn't affect trust, and consumer reviews don't influence buying intent. The researcher recommends that Sociolla price wisely and maintain brand image.